PERAN PENYULUH PERTANIAN DALAM MEMAJUKAN KELOMPOK TANI DI DESA CIPELANG, KABUPATEN BOGOR - Ergina, Gigi; Maad, Faizal; Suwarnata, Anak Agung Eka (Agrisintech (Journal of Agribusiness and Agrotechnology), 2022)
ABSTRACTStrengthening and developing farmer groups is a necessity in agricultural development which aims to increase agricultural productivity, fulfill national food needs, increase farmers' welfare, and realize national security stability. An element that plays an important role in the development of farmer groups is agricultural extension workers, namely as educators, facilitators, motivators, innovators and dynamicators for farmers both individually and in groups. Cipelang Village, Cijeruk District, has several farmer groups with different levels of activity. This study aims to analyze the role of agricultural extension workers in the development of farmer groups and the relationship between the role of agricultural extension workers and the development of farmer groups. The research population was lowland rice farmers, the determination of the number of research samples with the slovin formulation, and the sampling was done by simple random sampling. Primary data was collected through interviews with respondents using a questionnaire, while secondary data was collected from related agency documents and reports. Analysis of the role of agricultural extension workers in the development of farmer groups using descriptive statistical analysis and the relationship between the role of agricultural extension workers and the development of farmer groups was analyzed using Spearman rank correlation analysis. The results of the study indicate that the role of extension workers in the development of farmer groups is very high. The role of agricultural extension agents as facilitators, dynamists, motivators and educators is significantly related to the development of farmer groups, while the role of extension workers as innovators has not shown a significant relationship to the development of farmer groups.Â ABSTRAKPenguatan dan pengembangan kelompok tani merupakan kebutuhan dalam pembangunan pertanian yang bertujuan untuk meningkatkan produktifitas pertanian, pemenuhan kebutuhan pangan nasional, peningkatan kesejahteraan petani, dan secara lebih luas mewujudkan stabilitas ketahanan nasional. Salah satu elemen yang berperanan untuk pengembangan kelompok tani adalah penyuluh pertanian lapang, yaitu sebagai edukator, fasilitator, motivator, inovator dan dinamisator bagi petani baik secara individu maupun kelompok. Desa Cipelang, Kabupaten Bogor memiliki beberapa kelompok tani dengan tingkat keaktifan yang berbeda. Tujuan penelitian ini adalah menganalisis peran penyuluh pertanian lapang dalam pengembangan kelompok tani serta hubungan antara peran penyuluh pertanian dengan perkembanganÂ kelompok tani. Populasi penelitian adalah petani padi sawah, penentuan jumlah sampel penelitian dengan formulasi slovin, dan pengambilan sampel dilakukan dengan metode secara acak sederhana. Pengumpulan data primer dilakukan melalui wawancara terhadap responden dengan menggunakan kusioner, sedangkan data sekunder dari dokumen dan laporan intansi terkait. Analisis peran penyuluh pertanian lapangan menggunakan statistik deksriptif dan hubungan antara peran penyuluh pertanian lapangan dengan perkembangan kelompok tani dianalisis dengan menggunakan analisis korelasi rank spearman. Hasil penelitian menunjukkan bahwa peran penyuluh terhadap pengembangan kelompok tani tergolong sangat tinggi. Peran penyuluh pertanian lapang sebagai fasilitator, dinamisator, motivator dan edukator berhubungan signifikan dengan pengembangan kelompok tani, sementara itu peran penyuluh sebagai inovator belum menunjukan hubungan yang signifikan terhadap pengembangan kelompok tani.